2018
DOI: 10.1680/jgere.17.00019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consolidation on undrained behaviour of granular materials: experiment and DEM simulation

Abstract: The characteristic features of undrained responses of granular materials, for example, stress ratio at instability (η IS) and phase transformation (η PT) states and the critical state (CS) behaviour, are often influenced by the consolidation history. However, there are limited studies in the literature, and a consensus has not yet been reached. This study combined the triaxial test of yellow silty sand and the three-dimensional discrete element method (DEM) simulation of ellipsoid particles under a triaxial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This scenario is related to the interplay between the loading direction and the fabric anisotropy of the sand formed during sample preparation or natural deposition (Sivathayalan and Vaid 2002;Yang et al 2008;. Recent numerical studies by Nguyen et al (2017) and Rahman et al (2018) further indicated that the instability stress ratio of granular materials, which depends on both the state parameter and consolidation stress path, is closely related to the contact orientation of particles. Furthermore, during a cyclic triaxial loading test, such an anisotropic nature of pluviated or deposited sands leads to the following observation: in response to an applied symmetrical cyclic stress, the flow liquefaction of isotropically consolidated samples is typically initiated on the extension side of the stress pace.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is related to the interplay between the loading direction and the fabric anisotropy of the sand formed during sample preparation or natural deposition (Sivathayalan and Vaid 2002;Yang et al 2008;. Recent numerical studies by Nguyen et al (2017) and Rahman et al (2018) further indicated that the instability stress ratio of granular materials, which depends on both the state parameter and consolidation stress path, is closely related to the contact orientation of particles. Furthermore, during a cyclic triaxial loading test, such an anisotropic nature of pluviated or deposited sands leads to the following observation: in response to an applied symmetrical cyclic stress, the flow liquefaction of isotropically consolidated samples is typically initiated on the extension side of the stress pace.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies assessed liquefaction potential by considering the dissipated energy approach [1,12,[14][15][16][17][18]. Among the liquefaction assessment methods, the triaxial test is commonly adopted to predict the liquefaction potential under the critical state soil mechanics (CSSM) framework [2,3,5,[19][20][21][22][23][24]. Such a test is performed by controlling the principal stress and strain components in 3 orthogonal directions, where σ 11 and ε 11 are the major principal effective stress and strain, respectively, and σ 33 (equal to σ 22 ) and ε 33 (i.e., equal to ε 22 ) are the minor principal effective stress and strain, respectively.…”
Section: Introductionmentioning
confidence: 99%